Landscape heterogeneity shapes host‐parasite interactions and results in apparent plant–virus codivergence. Issue 8 (4th February 2013) - Rodelo‐Urrego, M.; Pagán, I.; González‐Jara, P.; Betancourt, M.; Moreno‐Letelier, A.; Ayllón, M. A.; Fraile, A.; Piñero, D.; García‐Arenal, F.
Abstract Knowledge on how landscape heterogeneity shapes host–parasite interactions is central to understand the emergence, dynamics and evolution of infectious diseases. However, this is an underexplored subject, particularly for plant–virus systems. Here, we analyse how landscape heterogeneity influences the prevalence, spatial genetic structure, and temporal dynamics of Pepper golden mosaic and Pepper huasteco yellow vein begomoviruses infecting populations of the wild pepper Capsicum annuum glabriusculum (chiltepin) in Mexico. Environmental heterogeneity occurred at different nested spatial scales (host populations within biogeographical provinces), with levels of human management varying among host population within a province. Results indicate that landscape heterogeneity affects the epidemiology and genetic structure of chiltepin‐infecting begomoviruses in a scale‐specific manner, probably related to conditions favouring the viruses' whitefly vector and its dispersion. Increased levels of human management of the host populations were associated with higher virus prevalence and erased the spatial genetic structure of the virus populations. Also, environmental heterogeneity similarly shaped the spatial genetic structures of host and viruses. This resulted in the congruence between host and virus phylogenies, which does not seem to be due to host‐virus co‐evolution. Thus, results provide evidence of the key role of landscape heterogeneity in determining plant–virus interactions.